The Effect of Reading Comprehension Ability to Mathematical Problem Solving Ability for Fifth Grade Students of Public Elementary Schools in Kebumen Sub-Distric in Academic Year of 2019/2020 - Frida Noor Afifah; Joharman Joharman; Rokhmaniyah Rokhmaniyah (Universitas Sebelas Maret, 2020)
The study aimed to prove significant and positive correlation between reading comprehension ability and mathematical problem solving ability and to determine the contribution of reading comprehension ability to mathematical problem solving ability for fifth grade students of public elementary schools in Kebumen sub-district in academic year 2019/2020. The research was a quantitative research with correlation method. The prerequisite test analysis used normality and linearity. Data analysis included simple correlation test and adjustes R square. The result indicates that there is positive and significant correlation between reading comprehension ability and mathematical problem solving ability. The correlation level is moderate which is 0.587 and the contribution of reading comprehension ability to mathematical problem solving ability is 25.8%. It concludes that there is positive and significant correlation between reading comprehension ability and mathematical problem solving ability for fifth grade students of public elementary schools in Kebumen sub-district in academic year of 2019/2020.